Internal audit function: a comparison between private and public sector in Nigeria - Madawaki, Abdulkadir; Ahmi, Aidi; Ahmad, Halimah @ Nasibah (EDP Sciences, 2017)
This study compares the internal audit functions between private and the public sector.Features examined include hierarchical rank of internal audit function, internal audit transfer, outsourcing of internal audit services and working relationship of internal audit with external auditor.The study is based on a survey of internal audit managers and chief internal auditors in private and public sector entities in Nigeria. The results revealed that there is no much difference in hierarchical rank of internal audit function in both sectors.While the results showed that differences exist in the reporting status between internal audit in the two sectors with private sector internal audit reporting to audit committee and chief executive officer and public sector internal audit reporting to chief executive officer and chief financial officer.Almost a similar amount of work is outsourced, and private sector entities are more likely to outsource than those in public sector.There is slight difference between internal audit activities and interaction with external auditor in the two sectors with private sector more likely to coordinate in the area of access to audit working papers.